NUMERICAL TREATMENT OF HIGHER ORDER DIFFERENTIAL EQUATIONS USING RUNGE KUTTA AND PREDICTOR CORRECTOR METHODS - AUDU, AMINU; KAMASKO, MARY; S.B. MUHAMMAD (BIMA JOURNAL OF SCIENCE AND TECHNOLOGY GOMBE, 2020)
In this study, two numerical methods were used to obtain a numerical solution of higher order ordinary differential equations. The two methods are the existing Runge Kutta method and Adam-Bashforth Moulton predictor corrector methods which have been modified to accommodate the general nth order ordinary differential equations. Four higher order differential equation problems were solved and the results obtained were consistent with when compared with the exact solution.